Avizandum Statutes on the Scots Law of Property, Trusts and Succession 2020-21. - Steven, Andrew (Edinburgh University Press, 2020)
This volume for Scots law students contains the main statutory provisions relating to both heritable and moveable property, trusts and succession. It includes all the important provisions regulating post-feudal land law in Scotland.